Creating the Future of Health The History of the Cumming School of Medicine at the University of Calgary, 1967-2012 - Lampard, Robert (University of Calgary Press, 2021)
Creating the Future of Health is the fascinating story of the first fifty years of the Cumming School of Medicine at the University of Calgary. Founded on the recommendation of the Royal Commission on Health Services in 1964 the Cumming School has, from the very beginning, focused on innovation and excellence in health education. With a pioneering focus on novel, responsive and systems-based approaches, it was one of the first faculties to pilot multi-year training programs in family medicine and remains one of only two three-year medical schools in North America. Drawing on interviews with key players and extensive research into documents and primary material, Creating the Future of Health traces the history of the school through the leadership of its Deans. This is a story of perseverance through fiscal turbulence, sweeping changes to health care and health care education, and changing ideas of what health services are and what they should do. It is a story of triumph, of innovation, and of the tenacious spirit that thrives to this day at the Cumming School of Medicine.